Analyzing Course Selection by MBTI Personality Types - Goo, Cui-Ling; Leow, Meng-Chew; Ong, Lee-Yeng (JOIV : International Journal on Informatics Visualization, 2025)
This research project explores the relationship between course selection and Myers-Briggs Type Indicator (MBTI) personality types. It focuses on a private university’s IT Faculty students pursuing AI, BIA, BIO, DCN, and ST courses. In higher education, there is a limited understanding of the influence of personality types on course selection. This research aims to determine the statistically significant differences between courses with personality profiles. To achieve this, data collected from the survey is systematically analyzed to provide useful insights into the distribution of course selection among various personality types through descriptive analysis and inferential statistics tests, such as the Kruskal-Wallis Test. These assessments help examine the statistically significant difference between courses for each personality profile, supported by a p-value < 0.05. Descriptive analysis shows INFJ typically occurred in every course, showing the wide distribution of this personality type among students. Besides, the result shows INF_ types predominantly appear in median personalities across all courses among the participants. The majority of the participants have INTP personality types. The inferential statistical results show statistically significant differences in the distribution of courses for 8 MBTI personality types, while the remaining MBTI is not statistically significant. The results also show statistically significant differences between courses for each personality dimension. These results can be used to provide suggestions to students on course selection. Future research could expand this study by including a more diverse range of universities and courses and incorporating additional personality assessments.